Factors Of Graduate Students' Attrition And Retention In Occidental Mindoro State College Graduate School - Casanova, Venessa S.; Luisa Pullido, Maria (International Journal of Educational Research & Social Sciences, 2022)
This case study was conducted to determine graduate students' attrition and retention factors and find ways to increase retention rates in the Occidental Mindoro State College (OMSC) Graduate School. A total of 31 purposively selected graduate students participated in the study. They were selected using the following inclusion criteria: they must be a graduate student of OMSC from AY 2015-2020, enrolled in any of the graduate school programs, has temporarily filed for a leave absence ( for attrition participants), and has finished their master's program ( for retention participants). A selfmade interview guide was the main instrument used in gathering data for the study. The data collected were coded to find frequencies of the themes out of the raw qualitative data. The study was conducted from February to August 2020 at the OMSC Main Campus, Labangan, Occidental Mindoro. It was found that financial constraints, school-work conflict, and personal problems were the factors identified for graduate students' attrition. On the other hand, job promotion, personal growth, and motivation were the factors for retention. At the same time, institutional and faculty support was the suggested way to increase graduate students' retention rate. It can be concluded thatfinancial constraints hinder graduate students from persisting and finishing their chosen degrees. Work-related factor promotes graduate student retention. Strategies employed by Higher Education Institutions play a vital role in increasing graduate students' retention rate.